THE INFLUENCE OF THE MOTIVE FOR THE USE OF AUDIO-VISUAL DA'WAH MEDIA ON INCREASING THE SATISFACTION OF DA'WAH MESSAGES IN SURABAYA ISLAMIC STUDENTS - Nanik Mujiati (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
The studies background of audio-visual media use as the da’wah media often accessed by Surabaya Islamic students. The study aims to see how the motive of the use of audio-visual da’wah media on the increasing satisfaction of the da’wah message on Surabaya Islamic students has been. Research answer the problems, 1) what was the motive behind the use of audio-visual da’wah media toward the increasing satisfaction of the da’wah message on Surabaya Islamic students? 2) what percentage of the motive behind the use of audio-visual da’wah media on the increasing satisfaction of the da’wah message on Surabaya Islamic students?. Data collection techniques this research through questionnaires, observation, interviews, and documentation. The technical data analysis is done in statistical quantitative. Based on research, it is known that there has been a significant influence on the use of audio-visual da’wah media toward the increased satisfaction of the da’wah message on Surabaya Islamic students. The motive for the use of audio-visual da’wah media on raising the satisfaction of the da’wah message on Surabaya Islamic students is 10,8 %. Keywords: Da’wah, Audio-visual Media, Da’wah Message.